A double blind placebo controlled study to determine the effects of intermittent cyclical etidronate on bone mineral density in patients on long term oral corticosteroid treatment - Pitt, P (BMJ Group, 1998)
BACKGROUND—A double blind, placebo controlled study was undertaken to determine the effects of 104 weeks of intermittent cyclical etidronate therapy on bone mineral density (BMD) in patients undergoing long term oral corticosteroid therapy. METHODS—Forty nine patients of mean age 59 years on long term (>6 months) corticosteroid treatment were randomised to receive either 400 mg/day etidronate or placebo for 14 days followed in both groups by calcium (equivalent to 97 mg elemental Ca/day) with vitamin D (400 IU) for 76 days. The cycle was repeated a total of eight times over a period of two years. Dual energy x ray absorptiometry (DEXA) measurements of the lumbar spine and hip BMD and biochemical bone marker analyses were performed at baseline and every six months. RESULTS—Twenty six patients (10 men) received cyclical etidronate and 23 (nine men) received placebo. The mean (SD) dose of corticosteroid (prednisone or equivalent) at baseline in the etidronate group was 8 (4) mg/day and in the placebo group was 7 (4) mg/day. Most of the patients (43%) suffered from asthma. Forty one patients completed the study (22 in the etidronate group and 19 in the placebo group). All had a low BMD at entry and with treatment a significant difference was observed between groups in the mean (SE) percentage change from baseline in lumbar spine BMD at week 104 of 4.5 (1.65)% (p = 0.007) with a 95% confidence interval (CI) of 1.12 to 7.87%. No clinically or statistically significant treatment differences were observed at the hip or with bone markers. The incidence of adverse events was similar in the two groups. CONCLUSIONS—The results show that intermittent cyclical etidronate therapy with calcium and vitamin D supplementation significantly increases lumbar spine BMD in patients with osteoporosis resulting from long term treatment with corticosteroids.